Desenvolvimento da cognição social em préescolares sob a ótica da teoria das molduras relacionais - Benatti, Lívia Andrade (2016)
Theory of Mind is conventionally defined as the ability to understand and make inferences about one’s own mental states (i.e., desires, intentions and beliefs) and those of other people, and based on this repertoire, one can predict and explain human behavior. Recent research, supported by Relational Frame Theory (RFT), has emphasized the role of perspective taking in the development of Theory of Mind. Results suggest that children who undergo perspective-taking training show improved performance in Theory of Mind tasks. The goal of the present study was to administer the Perspective Taking Protocol, used in these previous studies, in Brazilian children with low performance in theory of mind tasks. Three studies were conducted, two of them being pilot studies, which revealed the need for adaptations to the original procedure. Study 1 aimed to test the original protocol with one child aged 4 years and 9 months. The protocol consisted in the presentation of blocks of simple verbal trials and trials including reversal and double reversal of roles with the experimenter. Trials included the deictic frames I-YOU, HERE-THERE and NOW-THEN. The protocol, however, proved to be incompatible with the child’s repertoire, that is, he did not meet the learning criteria established in the original study. In order to test the difficulty level of the protocol, in Study 2, two young university students received the same training. Data suggested that the two adult participants succeeded in completing the protocol, having met criteria; however, they did face difficulties during the procedure. In Study 3, four participants, aged 4 and 5, were administered an adapted version of the protocol. In order to train reversed trials, physical tips (i.e., cards) and gestural signs were used and were gradually withdrawn until participants could respond without any assistance. Participants were also evaluated in three tasks of Theory of Mind, before and after the teaching procedure. During training, children were able to respond correctly on the reversed trials, even after removal of physical tips. All four participants showed improved performance in Theory of Mind tasks after training, with scores 1 or 2 points higher (scores could vary from 0 to 3), in comparison to pretest. Results suggest that, despite the evidence showing that the Perspective Taking Protocol is effective, it should be altered in order to be consistent with the repertoire of children with quite distinct characteristics from those who participated in the original study. In the case of children participating in the present research, changes in the distribution of trials throughout training blocks, as well as changes in the format of those trials had a positive learning effect. We hope the results of the present study may encourage future work on the potential benefits of procedures aimed at perspective taking training, in particular, with individuals who present delays or difficulties in social cognition.